OER as language online lessons to enhance Thai university students’ English language skills in the COVID-19 pandemic era - Budsaba - Kanoksilapatham, (Penerbit Universiti Kebangsaan Malaysia, 2021)
With the growth and widespread availability of education technologies, English language teaching (ELT) needs to be shaped differently. In addition, the COVID-19 pandemic has accelerated a disruption of education systems all over the world on a scale and scope never seen before. This paper aims to explore the potential of online lessons subcategorized as open educational resources (OER) in enhancing university students’ English language skills through the Moodle system. A total of 189 first-year humanities students from a medium sized university in Thailand participated in this study during a semester break. Prior to the OER exposure, the participants completed a questionnaire eliciting personal information, followed by a pre-test on five English language skills. Then, the students were encouraged to freely explore and exploit the online lessons for a period of 19 days. After the OER exposure, a parallel online post-test, a post OER exposure questionnaire, and semi-structured interviews were administered. The pre-test/post-test score comparison shows significant gain scores, suggesting the positive impact of the online lessons on the participants’ English performance. However, the questionnaire and interview data reveal intriguing findings about the students’ engagement and interaction with the online lessons, highlighting the notions of learner autonomy and self-regulated learning. This study, thus, represents a wake-up call for Thai ELT stakeholders to prepare to shift away from traditional teaching approaches, to modify teachers’ behaviours, syllabus, and curriculum, and to empower learners to successfully cope with the changing educational environment.